Probing the Ni2+‐selective Response of Fluorescent Probe NiSensor‐1 with the NiCast Photocaged Complex. (11th December 2021) - Hickey, Erin E.; Kennedy, Daniel P.; Gwizdala, Celina; Basa, Prem N.; Müller, Peter; MacDonald, John; Burdette, Shawn C.
Abstract: CTEA ( N, N ‐bis[2‐(carboxylmethyl)thioethyl]amine) is a mixed donor ligand that has been incorporated into multiple fluorescent sensors such as NiSensor‐1 that was reported to be selective for Ni 2+ . Other metal ions such as Zn 2+ do not produce an emission response in aqueous solution. To investigate the coordination chemistry and selectivity of this receptor, we prepared NiCast, a photocage containing the CTEA receptor. Cast photocages undergo a photoreaction that decreases electron density on a metal‐bound aniline nitrogen atom, which shifts the binding equilibrium toward unbound metal ion. The unique selectivity of CTEA was examined by measuring the binding affinity of NiCast and the CTEA receptor for Ni 2+, Zn 2+, Cd 2+ and Cu 2+ under different conditions. In aqueous solution, Ni 2+ binds more strongly to the aniline nitrogen atom than Cd 2+ ; however, in CH3 CN, the change in affinity virtually disappears. The crystal structure of [Cu(CTEA)], which exhibits a Jahn–Teller–distorted square pyramidal structure, was also analyzed to gain more insight into the underlying coordination chemistry. These studies suggest that the fluorescence selectivity of NiSensor‐1 in aqueous solution is due to a stronger interaction between the aniline nitrogen atom and Ni 2+ compared to other divalent metal ions except Cu 2+ . Abstract : NiSensor‐1, which contains a CTEA receptor, produces a selective emission response for Ni 2+ . To investigate the coordination chemistry and selectivity of CTEA, we prepared NiCast, an o ‐nitrobenzyl photocage. In aqueous solution, Ni 2+ binds more strongly to the aniline nitrogen atom than metal ions other than Cu 2+ ; however, in CH3 CN, the change in affinity virtually disappears. These studies suggest that the fluoresence selectivity of NiSensor‐1 in aqueous solution is due to a stronger interaction between the aniline nitrogen atom and Ni 2+ but not necessarily the receptor.